2011
DOI: 10.2147/ijgm.s15818
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus, insulin resistance, and metabolic syndrome in HIV-positive patients in South India

Abstract: Insulin resistance, diabetes mellitus, and metabolic syndrome in patients with human immunodeficiency virus (HIV) infection are increasingly being reported in the global medical literature. This cross-sectional study was done to describe the occurrence of metabolic syndrome, diabetes mellitus, and insulin resistance in HIV-positive patients in a tertiary referral center in South India. A total of 60 patients who had HIV infection for 12 months or more were enrolled in the study. Of these, 30 patients were anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 17 publications
3
47
1
Order By: Relevance
“…Some studies in Thailand reported a similar rate of dyslipidemia at 53.6% and 88% [38,50]. Other studies from other developing countries showed similar results oh high prevalence lipid abnormalities rate of more than 76% [35] from Tanzania, 82.3% [19] from Southern Ethiopia, 20-100% from India [7,41]. …”
Section: Discussionmentioning
confidence: 75%
“…Some studies in Thailand reported a similar rate of dyslipidemia at 53.6% and 88% [38,50]. Other studies from other developing countries showed similar results oh high prevalence lipid abnormalities rate of more than 76% [35] from Tanzania, 82.3% [19] from Southern Ethiopia, 20-100% from India [7,41]. …”
Section: Discussionmentioning
confidence: 75%
“…There was a significant association between abdominal obesity (a surrogate for clinical insulin resistance in this ethnic group), peripheral obesity, and exposure to ART. Although the mechanisms of action by which protease inhibitors and nucleoside analogs trigger diabetes is not fully understood, most of the hypothesized pathophysiology implicates the insulin resistance pathway16,17 rather than insulin secretion 38…”
Section: Discussionmentioning
confidence: 99%
“…However, older age, HIV infection itself, antiretroviral therapy (ART), HIV-related inflammation, current CD4 T cell count, nadir CD4 T cell count < 350 cells/mm 3 , and traditional risk factors for cardiovascular disease (smoking, obesity, physical inactivity, excess alcohol intake) substantially increase the risk of cardiovascular disease, including hypertension, stroke, coronary artery disease, peripheral artery disease, dyslipidemia, diabetes mellitus, metabolic syndrome, and lipodystrophy 517…”
Section: Introductionmentioning
confidence: 99%
“…Also, early reports in 2000 on the side effects of PIs highlighted the incidence of high concentrations of the lipid profile as being close to 80% [77][78][79] in various global populations, mostly from I. In Asia, in particular Southeast Asia, Thailand [91][92][93][94][95], and India [96][97][98], HIV-associated serum lipid complication rates are in the range of 5-60% for high TC, high LDL-c, high TG, and low HDL among ART receivers. Fewer studies have been conducted in some regions in South America and Asia on the relationship between metabolic disorders and ART.…”
Section: Epidemiologymentioning
confidence: 99%